The Role of Triple Bottom Line Accounting in Advancing Sustainable Development - Kartiko, Erik; Ningsih, Winda; Merliyana, Reny Dany (Indonesian Scientific Publication, 2024)
Global demand for sustainability reporting has elevated Triple Bottom Line (TBL) accounting as a key framework that integrates financial, social, and environmental accountability. This review synthesizes research published between 2010 and 2024 to evaluate how TBL has been adopted, its effectiveness, and its limitations across regions and sectors. The study highlights that TBL adoption improves firm performance through profitability, stakeholder engagement, and ecological responsibility. Developed economies show stronger integration due to regulatory and market support, while developing economies face institutional and resource challenges. High-carbon industries struggle to adopt TBL comprehensively, whereas environmentally oriented sectors use it to innovate and increase efficiency. The review identifies regulation, consumer demand, and managerial capacity as critical drivers of success. It also emphasizes the need for standardized metrics, stronger adoption in emerging markets, and exploration of digital technologies to enhance practice. By comparing contexts, this study contributes a global perspective and underscores TBL as a strategic tool for sustainable corporate governance and long-term value creation.